NLRP3 Inflammasome Inhibition After Pilocarpine-Induced Status Epilepticus Attenuates Chronic Inflammation in Epileptic Mice - Wang L; Wang K; Chen Y; Zhang X; Xu W; Dong Z; Wang Y (Dove Medical Press, 2024)
Lei Wang,1,* Kai Wang,2,* Yuwen Chen,1 Xiaoyu Zhang,1,3 Wenhao Xu,1,3 Zhong Dong,1,3 Yu Wang1,3,4 1Department of Neurology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, 230000, People's Republic of China; 2Department of Neurology, The Third Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, 230000, People's Republic of China; 3Department of Neurology, Anhui Public Health Clinical Center, Hefei, Anhui Province, 230000, People's Republic of China; 4Department of Neurology, Anqing First People's Hospital Affiliated to Anhui Medical University, Anqing, Anhui Province, 246000, People's Republic of China*These authors contributed equally to this workCorrespondence: Yu Wang, Department of Neurology, The First Affiliated Hospital of Anhui Medical University, Hefei, Anhui Province, 230000, People's Republic of China, Email yw4d@hotmail.comObjective: To investigate the effects of inhibiting the NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasome on neuronal damage and chronic pro-inflammatory responses during epileptogenesis in a mouse model of pilocarpine-induced status epilepticus (SE).Methods: Mice were randomly allocated into three groups: control, SE, and SE + MCC 950. The expression patterns of M1 and M2 microglial biomarkers in the hippocampus were quantified using Western blotting, quantitative real-time polymerase chain reaction, enzyme-linked immunosorbent assay, and immunofluorescence staining. Additionally, seizure susceptibility, video-electroencephalography recording, Morris water maze test, and brain immunofluorescence staining were performed to evaluate the epileptic brain 4 weeks post-SE.Results: Within 72 hours post-SE, hippocampal microglia demonstrated a preferential polarization towards the M1 phenotype, a trend that was mitigated by NLRP3 inflammasome inhibition. During epileptogenesis, SE mice treated with NLRP3 inflammasome inhibition exhibited reduced neuronal damage, improved cognitive function, decreased seizure susceptibility, and attenuated chronic pro-inflammatory responses.Conclusion: Inhibition of NLRP3 inflammasome post-SE effectively ameliorates neuronal loss, seizure susceptibility, and cognitive dysfunction during epileptogenesis. This neuroprotective effect may be mediated through the mitigation of chronic pro-inflammatory responses within the epileptic brain.Keywords: NLRP3 inflammasome, microglial polarization, M1 microglia, epileptogenesis, chronic pro-inflammatory response